Distinct regions within the GluN2C subunit regulate the surface delivery of NMDA receptors - Lichnerova, Katarina; Kaniakova, Martina; Skrenkova, Kristyna; Vyklicky, Ladislav; Horak, Martin (Frontiers in Cellular Neuroscience, 2014)
N-methyl-D-aspartate (NMDA) receptors mediate fast excitatory synaptic transmission in the mammalian central nervous system. The activation of NMDA receptors plays a key role in brain development, synaptic plasticity, and memory formation, and is a major contributor to many neuropsychiatric disorders. Here, we investigated the mechanisms that underlie the trafficking of GluN1/GluN2C receptors. Using an approach combining molecular biology, microscopy, and electrophysiology in mammalian cell lines and cultured cerebellar granule cells, we found that the surface delivery of GluN2C-containing receptors is reduced compared to GluN2A- and GluN2B-containing receptors. Furthermore, we identified three distinct regions within the N-terminus, M3 transmembrane domain, and C-terminus of GluN2C subunits that are required for proper intracellular processing and surface delivery of NMDA receptors. These results shed new light on the regulation of NMDA receptor trafficking, and these findings can be exploited to develop new strategies for treating some forms of neuropsychiatric disorders.